2018
DOI: 10.1099/mgen.0.000214
|View full text |Cite
|
Sign up to set email alerts
|

The return of Pfeiffer’s bacillus: Rising incidence of ampicillin resistance in Haemophilus influenzae

Abstract: Haemophilus influenzae, originally named Pfeiffer’s bacillus after its discoverer Richard Pfeiffer in 1892, was a major risk for global health at the beginning of the 20th century, causing childhood pneumonia and invasive disease as well as otitis media and other upper respiratory tract infections. The implementation of the Hib vaccine, targeting the major capsule type of H. influenzae, almost eradicated the disease in countries that adapted the vaccination scheme. However, a rising number of infections are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 106 publications
0
24
1
2
Order By: Relevance
“…According to WHO estimates, approximately 65 million people have moderate to severe COPD. Over 3 million people died of COPD in 2005, which corresponded to 5% of all deaths globally ( 7 ). Invasive disease caused by NTHi has increased significantly in recent years, in part as a result of broad usage of vaccines against Haemophilus influenzae type b and Streptococcus pneumoniae ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO estimates, approximately 65 million people have moderate to severe COPD. Over 3 million people died of COPD in 2005, which corresponded to 5% of all deaths globally ( 7 ). Invasive disease caused by NTHi has increased significantly in recent years, in part as a result of broad usage of vaccines against Haemophilus influenzae type b and Streptococcus pneumoniae ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that the prevalence of Hib carriage in children has decreased to \ 1% in the vaccine era [28]. Furthermore, substantial shifts in the epidemiology of invasive HI disease have been observed, with nontypeable HI (NTHi) becoming the main pathogenic lineage in post-Hib vaccination settings [29][30][31]. In contrast to Hib, which in the prevaccine era caused invasive disease mostly in healthy children aged \ 5 years, invasive NTHi infections occur mainly in neonates and the elderly and commonly in the presence of predisposing medical conditions [32].…”
Section: Haemophilus Influenzaementioning
confidence: 99%
“…Se ha comprobado sobre todo en los pacientes con fibrosis quística o con EPOC con colonización con P. aeruginosa [ 47 ]. Otras situaciones en las que es fácil objetivar el problema de la selección de mutantes resistentes es la que se presenta en los aislados de H. influenzae con mutaciones en la PBP3 (gen fstl ) [ 36 , 58 ]. Estos aislados pierden sensibilidad a las cefaloporinas orales como cefuroxima y cefixima y cuando los aislados además producen betalactamasas (aislados BLPACR) pierden también sensibilidad amoxicilina-ácido clavulánico y en mucha menor medida las cefalosporinas de uso intravenoso, cefotaxima y ceftriaxona, y la oral cefditoreno [ 36 , 38 ].…”
Section: Ventana De Selección Y Concentración Que Previene La Apariciunclassified